(untitled) (American Journal of Language, Literacy and Learning in STEM Education (2993-2769), 2024)
Distance education (DL) is a means of providing students with the main part of the studied material, interactive interaction of students and teachers in the educational process, mastering of the studied material. is a set of technologies that enable independent work for This education is provided by various means of mutual communication during the educational process.